Isethionate formation from taurine in Chromohalobacter salexigens: purification of sulfoacetaldehyde reductase - Krejčík, Zdeněk; Hollemeyer, Klaus; Smits, Theo H M; Cook, Alasdair M (Microbiology (Reading, England), 2010)
Bacterial generation of isethionate (2-hydroxyethanesulfonate) from taurine (2-aminoethanesulfonate) by anaerobic gut bacteria was established in 1980. That phenomenon in pure culture was recognized as a pathway of assimilation of taurine-nitrogen. Based on the latter work, we predicted from genome-sequence data that the marine gammaproteobacterium Chromohalobacter salexigens DSM 3043 would exhibit this trait. Quantitative conversion of taurine to isethionate, identified by mass spectrometry, was confirmed, and the taurine-nitrogen was recovered as cell material. An eight-gene cluster was predicted to encode the inducible vectorial, scalar and regulatory enzymes involved, some of which were known from other taurine pathways. The genes (Csal_0153-Csal_0156) encoding a putative ATP-binding-cassette (ABC) transporter for taurine (TauAB(1)B(2)C) were shown to be inducibly transcribed by reverse transcription (RT-) PCR. An inducible taurine : 2-oxoglutarate aminotransferase [EC 2.6.1.55] was found (Csal_0158); the reaction yielded glutamate and sulfoacetaldehyde. The sulfoacetaldehyde was reduced to isethionate by NADPH-dependent sulfoacetaldehyde reductase (IsfD), a member of the short-chain alcohol dehydrogenase superfamily. The 27 kDa protein (SDS-PAGE) was identified by peptide-mass fingerprinting as the gene product of Csal_0161. The putative exporter of isethionate (IsfE) is encoded by Csal_0160; isfE was inducibly transcribed (RT-PCR). The presumed transcriptional regulator, TauR (Csal_0157), may autoregulate its own expression, typical of GntR-type regulators. Similar gene clusters were found in several marine and terrestrial gammaproteobacteria, which, in the gut canal, could be the source of not only mammalian, but also arachnid and cephalopod isethionate.
Keywords: Chromohalobacter; bakteriální proteiny; Reverse Transcriptase Polymerase Chain Reaction; multigenová rodina; Marinomonas; Isethionic Acid; Klebsiella oxytoca; Taurine; isomerie; metabolické sítě a dráhy; kyselina isethionová; Amination; elektroforéza v polyakrylamidovém gelu; polymerázová řetězová reakce s reverzní transkripcí; Electrophoresis, Polyacrylamide Gel; Bacterial Proteins; Genes, Bacterial; Metabolic Networks and Pathways; Isomerism; Multigene Family; izoenzymy; Isoenzymes; aminace; bakteriální geny; taurin